2017
DOI: 10.1002/ldr.2690
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Sediment Sources Using Mid‐infrared Spectroscopy in Arvorezinha Catchment, Southern Brazil

Abstract: The widespread adoption of the sediment fingerprinting approach to guide catchment management has been limited by the cost and the difficulty to prepare and process samples for geochemical and radionuclide analyses. Spectral properties have recently been shown to provide a rapid and cost‐efficient alternative for this purpose. The current research objective was (i) to quantify the sediment source contributions in a 1∙19‐km2 rural catchment of Southern Brazil by using mid‐infrared (MIR) spectroscopy and (ii) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…River systems are influenced by climate, tectonic and anthropogenic impacts (Macklin & Lewin, ) which cause fluctuations in fluvial morpho‐dynamics and sediment composition (Hoffmann et al ., , ; Erkens et al ., ). Determining sediment provenance is thus an important tool to understand the evolution of fluvial environments at short timescales (Poulenard et al ., , ; Evrard et al ., ; Palazón et al ., ; Tiecher et al ., ) middle timescales (for example, millennia, Holocene period, Owens et al ., ; Foster et al ., , ; Hatfield & Maher, ) and long timescales (for example, Quaternary and pre‐Quaternary periods, Hagedorn & Boenigk, ; Suresh et al ., ; Mange & Otvos, ). Characterizing sediment sources is crucial to determine time‐transgressive changes in sediment provenance from sedimentary deposits (Sircombe, ).…”
Section: Introductionmentioning
confidence: 99%
“…River systems are influenced by climate, tectonic and anthropogenic impacts (Macklin & Lewin, ) which cause fluctuations in fluvial morpho‐dynamics and sediment composition (Hoffmann et al ., , ; Erkens et al ., ). Determining sediment provenance is thus an important tool to understand the evolution of fluvial environments at short timescales (Poulenard et al ., , ; Evrard et al ., ; Palazón et al ., ; Tiecher et al ., ) middle timescales (for example, millennia, Holocene period, Owens et al ., ; Foster et al ., , ; Hatfield & Maher, ) and long timescales (for example, Quaternary and pre‐Quaternary periods, Hagedorn & Boenigk, ; Suresh et al ., ; Mange & Otvos, ). Characterizing sediment sources is crucial to determine time‐transgressive changes in sediment provenance from sedimentary deposits (Sircombe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the DRIFTS spectra of the sediment source samples, 17 characteristic absorption peaks were identified that are typical for soil samples (Figure ; Tiecher et al, ). The 3,695 and 3,620 cm −1 peaks are characteristic for aluminosilicates (kaolinite and micas), which are typically present in clays (Parikh, Goyne, Margenot, Mukome, & Calderón, ; Poulenard et al, ; Tiecher et al, ; Yang & Mouazen, ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the DRIFTS spectra of the sediment source samples, 17 characteristic absorption peaks were identified that are typical for soil samples (Figure ; Tiecher et al, ). The 3,695 and 3,620 cm −1 peaks are characteristic for aluminosilicates (kaolinite and micas), which are typically present in clays (Parikh, Goyne, Margenot, Mukome, & Calderón, ; Poulenard et al, ; Tiecher et al, ; Yang & Mouazen, ). The peaks around 2,920 and 2,850 cm −1 are generally attributed to organic matter (Poulenard et al, ; Reeves III, ; Tiecher et al, ), whereas the peak at 2,505 cm −1 is attributed to carbonates (inorganic carbon; Poulenard et al, ; Reeves III, Mccarty, & Reeves, ; Viscarra Rossel et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Franz et al ., ; Palazón et al ., ; Chen et al ., ; Vale et al ., ; Tiecher et al ., ), which has evolved significantly over the past decades as a method to estimate sediment source contributions directly from river sediment (Davis and Fox, ; Mukundan et al ., ; Owens et al ., ; Pulley and Collins, ). Particularly interesting from a monitoring perspective is the recent development of methods based on infrared spectrometry (Poulenard et al ., ; Cooper et al ., ; Tiecher et al ., ), which are more time‐ and cost‐effective compared to traditional geochemical sediment fingerprinting methods (Collins et al ., ). These advancements enable sediment fingerprinting to be easier applied at a finer temporal frequency (i.e.…”
Section: Introductionmentioning
confidence: 99%